Uncertainty over lorry brake checks - Gimino, Gerard; Meng, Yew Choong (2026)
Transport ope- rators are asking for more clarity over the enforcement of the new brake parameter for lorries, saying more engagement is needed before its planned rollout on March 1. While supporting efforts to enhance road safety, Selangor and Kuala Lumpur Lorry Operators Association secretary-general Alvin Choong said older lorries may require major modifications to comply with the ruling. He also proposed a phased enforcement period, beginning with newer trucks, to allow older vehicles to adjust accordingly. According to Choong, most commercial vehicle operators are in the dark on this, with little to no information given on the requirement.